Agent Orange footprint still visible in rural areas of central Vietnam - Banout, Jan; Urban, Ondrej; Musil, Vojtech; Szakova, Jirina; Balik, Jiri (Journal of environmental and public health, 2014)
Levels of polychlorinated dioxins/furans (PCDD/PCDF) in selected environmental samples (soils, sediments, fish, and farm animals) were analyzed from the area of Phong My commune (Thua Thien-Hue province, Vietnam). This area was affected by Agent Orange spraying during the Vietnam war (1968-1971). Whereas PCDD/PCDF content in soil and sediment samples is relatively low and ranges between 0.05 and 5.1 pg WHO-TEQ/g for soils and between 0.7 and 6.4 pg WHO-TEQ/g for sediments, the PCDD/PCDF content in poultry muscle and liver in most cases exceeded the maximum permissible limit of dioxin content per unit fat mass. In some cases of soil and sediments samples, 2,3,7,8-TCDD represented more than 90% of the total PCDD/PCDF, which indicates Agent Orange as the main source.
Keywords: Fishes; Defoliants, Chemical; Polychlorinated Dibenzodioxins; lidé; Agent Orange; Dioxins; ryby; polychlorované dibenzodioxiny; chemické defolianty; Gas Chromatography-Mass Spectrometry; kyselina 2,4-dichlorfenoxyoctová; Humans; Environmental Pollutants; 2,4,5-Trichlorophenoxyacetic Acid; plynová chromatografie s hmotnostně spektrometrickou detekcí; monitorování životního prostředí; Environmental Monitoring; 2,4-Dichlorophenoxyacetic Acid; zvířata; dioxiny; kyselina trichlorfenoxyoctová; Vietnam; Animals; Livestock; látky znečišťující životní prostředí; furany; dobytek; Furans